The potential impact of diving charges on the demand for diving and the diving industry in the Aliwal Shoal Marine Protected Area: a pilot study - Schmidt, Jadon (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
This research is presented in three sections. Section 1 presents the research report in an Academic Paper format. Section 2 provides a comprehensive literature review and Section 3 describes the research methodology and methods employed. Sustainable management of natural resources is a global imperative. It is particularly significant in a country like South Africa that is blessed with an abundance of biological diversity but faces many socio economic challenges that are associated with developing nations. Toward addressing these issues, diver permit fees were implemented in South Africa in 2005, making it a legal requirement for all scuba divers undertaking a dive in a Marine Protected Area (MPA) to purchase a permit. This pilot study is the first attempt since the inception of the dive permit fees to determine their impact on the demand for diving and the diving industry in the Aliwal Shoal MPA, one of the premier dive destinations in the country. In order to address key questions, qualitative data was gathered during interviews with 12 dive operators active in the MPA and 28 divers that utilised the operators to dive. In addition, independent quantitative data on the number of dive boat launches during the past 20 years was used in conjunction with mean paying diver data obtained from the operators to ascertain the demand for diving at the Aliwal Shoal during the past two decades. Results indicate that were no significant differences (at the 5% level of significance) between paying divers during 2005 compared to 2004 and 2006 [H =.1923366, N= 36, p =0.9083]. Paying diver data for the period 2000 - 2004 were compared to 2005 - 2010 and no significant differences were found at the 5% level of significance (U= 2040, Npost = 72, Npre= 60, p = 0.584981). Diver interviews revealed that only 36% of divers had paid for a permit, representing a loss of R7 438 499 during the past five years, enough to support the current budget of the MPA for 10.6 years. Operator interviews revealed that alternative destinations, economic climate and local competition had the most impact on their businesses, with permit fees having no impact on the 50% of the operators' businesses. Operators also reported that there was little or no enforcement of the permit fees, 9 of the operators indicated that there has been no improvement in the MPA or its management since the inception of the fees and all were dissatisfied with the current management MPA. Operators and divers complained about the current purchasing and handling practices associated with the permits. Despite offering a world class diving opportunity, the dive operators currently have no incentive to enforce the permit system and due to price pressure in the local market, and have adopted a mute stance on diver permits. Consequently, there has been no significant impact on the demand for diving since the inception of the permits in 2005. The initial hypothesis that the increased costs to divers as a result of the permits would drive down the demand for diving is therefore rejected. If the permits are more strictly enforced, it is likely that more divers may seek alternative destinations due to the perception of poor value as a result of the Sappi Saiccor effluent discharge, existence of shark nets and poor management, in accordance with existing literature. The resultant decrease in demand will be detrimental to the diving industry at Aliwal Shoal. The second hypothesis, that the costs associated with the better enforcement of the MPA regulations-in terms of impacts on the diving industry- might outweigh the benefits, is therefore accepted. All the results produced by this study suggest that authorities may have been too enthusiastic to have all the boxes ticked in order to meet deadlines for international targets for marine conservation and paid little or no attention to lessons learnt from MPAs globally. Every negative aspect highlighted by existing international literature as symptomatic of MPA failure is occurring at Aliwal Shoal MPA, albatrossing it with "paper park" status. Due to the size and scope of this study, the results should be interpreted with caution and not be utilised to guide policy but rather encourage further research.
Keywords: Marine parks and reserves -- South Africa -- KwaZulu-Natal; Recreational dive industry -- South Africa -- KwaZulu-Natal; Recreational dive industry -- Licenses -- South Africa -- KwaZulu-Natal; Marine parks and reserves -- South Africa -- KwaZulu-Natal -- Management; Conservation of natural resources -- South Africa -- KwaZulu-Natal; Environmental management -- South Africa -- KwaZulu-Natal; Marine resources conservation -- South Africa -- KwaZulu-Natal; Waste disposal in the ocean -- South Africa -- KwaZulu-Natal; Marine pollution -- South Africa -- KwaZulu-Natal